2016
DOI: 10.1080/00036846.2016.1158917
|View full text |Cite
|
Sign up to set email alerts
|

Crises and exchange rate regimes: time to break down the bipolar view?

Abstract: Avertissement :Les commentaires et analyses développés n'engagent que leurs auteurs qui restent seuls responsables des erreurs et insuffisances. AbstractWe revisit the link between crises and exchange rate regimes (ERR). Using a panel of 90 developed and developing countries over the period 1980-2009, we find that corner ERR are not more prone to crises compared to intermediate ERR. This finding holds for different types of crises (banking, currency and debt), and is robust to a wide set of alternative specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…They found that institutions are weaker in periods before and after a currency crisis than during tranquil periods. Finally, Combes, Minea, and Sow () using a panel of 90 developed and developing countries over the period 1980–2009, found that corner exchange rate regimes are not more prone to crises compared to intermediate exchange rate regimes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that institutions are weaker in periods before and after a currency crisis than during tranquil periods. Finally, Combes, Minea, and Sow () using a panel of 90 developed and developing countries over the period 1980–2009, found that corner exchange rate regimes are not more prone to crises compared to intermediate exchange rate regimes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ghosh and Ostry (2009) go even further by proving that intermediate regimes represent the balance between pegs and free floats and are associated with faster per capita output growth. Esaka (2010) and Combes and Swo (2016) criticise the bipolar view underlining the fact that it does not strictly hold in the sense that intermediate regimes are significantly more prone to currency crises than corner regimes. Therefore monetary authorities in emerging and developing economies often try to smooth exchange rate path without an official commitment to maintain the official central exchange rate (Ötker-Robe & Vávra, 2007), or claim to have a pegged exchange rate while carrying out frequent changes in the official exchange rate (Alesina & Wagner, 2006;Genberg & Swoboda, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The main issue of concern is whether the choice of exchange rate regime has a significant influence on the interaction among these macroeconomic variables. While some studies find empirical support for the view that the choice of regime plays a neutral role and does not change the behaviour of macroeconomic variables (Baxter and Stockman, 1989;Combes et al, 2016;Dedola and Leduc, 1999;Singh, 2002), others find support that the choice of exchange rate regime does indeed matter (Edwards and Yeyati, 2005;Egwaikhide et al, 2014;Erdem and Omen, 2015;Levy-Yeyati and Sturzenegger, 2003;Ye et al, 2014). Baxter and Stockman (1989), examine the performance of output, consumption, trade flows, government consumption and real exchange rates under alternative exchange-rate regimes using a sample of 49 countries.…”
Section: The Review Of Related Literaturementioning
confidence: 99%
“…They find evidence of regime neutrality and that changes in the mean of most of the macroeconomic variables are not significantly different from each other under the de facto regimes. Combes et al (2016), examine the link between exchange rate regime and crisis in both developed and developing countries from 1980 to 2009. Consistent with the regime neutrality theory, they find that the choice of exchange rate regime plays unimportant role when it comes to the likelihood of crisis irrespective of the type of crisis (banking, currency or debt crisis).…”
Section: Studies Supporting the Neutrality Viewmentioning
confidence: 99%
See 1 more Smart Citation